Navigating old age and the urban terrain: Geographies of ageing from Africa. (August 2021) - McQuaid, Katie; Esson, James; Gough, Katherine V.; Wignall, Ross
This paper extends research on geographies of ageing in relation to urban academic and policy debates. We illustrate how older people in urban African contexts deploy their agency through social and spatial (im)mobilities, intergenerational relations and (inter)dependencies. Through doing so, we reveal how urban contexts shape, and are shaped by, older people's tactics for seizing opportunities and navigating the urban terrain. Our analysis demonstrates how a more substantive dialogue between insights on ageing in African contexts and urban ageing policy can create new forms of knowledge that are more equitable and just, both epistemologically and in their policy impacts.